KOMBINASI LATIHAN HOLD RELAX DAN AUTO MYOFASCIAL RELEASE TECHNIQUE LEBIH MENURUNKAN NYERI OTOT BETIS DARIPADA LATIHAN HOLD RELAX DAN AUTO STRETCHING PADA KARYAWAN SALES PROMOTION GIRLS (SPG) DI LIPPO MALL KUTA BALI - I.A. Pascha Paramurthi; Luh Made Indah Sri Handari Adiputra; M.Ali Imron; Desak Made Wihandani; Made Muliarta; Sugijanto - (Sport and Fitness Journal, 2018)
Background: Calf Muscle Pain is discomfort and pain feeling in the gastrocnemius and soleus muscles, a result of constantly receiving the loading due to excessive wear. Purpose: This study was to determine hold relax exercise and auto myofascial release technique was more effective to reduce calf muscle pain than hold relax and auto stretching on SPG at Lippo Mall Kuta Bali. Methods: This research was an experimental study with pre and post test control group design. Total sample of this study were 22 SPGs, which divided into 2 groups. Group 1 (n = 11) was given hold relax exercise and auto stretching while the group 2 (n = 11) was given intervention hold relax exercise and auto myofascial release technique. Do exercise 3 times a week for 4 weeks. Sampling techniques with random sampling. Calf muscle pain was measured with modification sphygmomanometer to provoked pain. Result: Group 1 result obtained p value = 0,001 (p <0.05) and in Group 2 got result obtained p value = 0.001 (p<0.05) for Paired Sample T-test. Different test of mean value with independent sample t-test after treatment found that the decrease of calf muscle pain in group 2 was 232.73 mmHg better than group 1 was 199.09 mmHg with p value = 0.035 (p <0.05). Conclusion: Hold relax exercise and auto myofascial release technique more effective to reduce calf muscle pain than hold relax exercise and auto stretching on SPGs in Lippo Mall Kuta Bali. Suggestion: For the next researcher can do follow up research to see long-term result of hold relax and auto stretching exercise as well hold relax and auto myofascial release technique for SPGs.